POLA PENGEMUDI YANG MENINGGAL AKIBAT KECELAKAAN DI JALAN DI NEGARA-NEGARA EROPA - Narendra, Alfa (Menara: Jurnal Teknik Sipil, 2023)
This paper aims to provide an overview of the relationship pattern of the number of drivers who died due to road accidents related to the number of pedestrians, injured people, people died from road accidents, population, total population density and length of road vehicles in European countries with different income levels. The method used is descriptive statistics and statistical analysis was described through a boxplot. The relationship between the number of drivers and the number of pedestrians who die from road accidents, shows an inverse relationship in upper-middle-income European countries. Meanwhile, high-income and lower-middle-income European countries show a unidirectional relationship. Relationship between the number of drivers, the number of people killed and the number of people injured in road accidents, shows a unidirectional relationship. This occurs in high-income, upper-middle and lower-income countries. The relationship between the number of drivers who died due to road accidents and the population, showed an inverse relationship occurred in upper and lower middle-income European countries. Meanwhile, high-income European countries show a unidirectional relationship. The relationship between the number of drivers who died as a result of road accidents, the number of population density and the length of the road vehicles, showed an inverse relationship occurred.